Omega-3 Fatty Acids Alter Systemic Inflammatory Mediators Caused by Apical Periodontitis - Azuma, Mariane Maffei [UNESP]; Cardoso, Carolina de Barros Morais [UNESP]; Samuel, Renata Oliveira [UNESP]; Pipa, Camila Barbosa [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Narciso, Luis Gustavo [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier, 2021)
Introduction: This study investigated the effects of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) on serum inflammatory mediators of rats with pulp exposure–induced apical periodontitis. Methods: Forty male Wistar rats were divided into the following groups: control, untreated rats (C); control rats treated with ω-3 PUFAs (C-O); rats with pulp exposure–induced apical periodontitis (AP); and rats with pulp exposure–induced apical periodontitis treated with ω-3 PUFAs (AP-O). ω-3 PUFAs were administered orally once a day for 15 days before pulp exposure and continued for 30 days after pulp exposure. The rats were sacrificed, and then blood and jaw samples were collected. Blood analysis was conducted to determine the total number of leukocytes including neutrophils, monocytes, and lymphocytes. Proinflammatory cytokines tumor necrosis factor alpha, interleukin (IL) 6, and IL-17 were quantified by enzyme-linked immunosorbent assay. Histologic analysis was performed to confirm the development of apical periodontitis. The data were statistically evaluated using analysis of variance and the Tukey posttest. The significance level was set at 5%. Results: The development of apical periodontitis was confirmed in all infected groups. Bone destruction was larger in the AP group compared with the AP-O group (P <.05). Blood analysis showed that the AP and AP-O groups showed higher numbers of lymphocytes, leukocytes, monocytes, eosinophils, and expressions of tumor necrosis factor alpha and IL-6 compared with the C and C-O groups (P <.05). In contrast, the presence of leukocytes, lymphocytes, and the expression of IL-6 decreased in the AP-O group compared with the AP group (P <.05). Conclusions: ω-3 PUFA supplementation influences the systemic effects caused by apical periodontitis, decreasing the number of leukocytes, lymphocytes, and IL-6 in rat blood.
Keywords: Apical periodontitis; endodontic infection; endodontic medicine; omega-3 fatty acids